2014
DOI: 10.1016/j.neuropsychologia.2014.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Multiple forms of contour grouping deficits in schizophrenia: What is the role of spatial frequency?

Abstract: Schizophrenia patients poorly perceive Kanizsa figures and integrate co-aligned contour elements (Gabors). They also poorly process low spatial frequencies (SFs), which presumably reflects dysfunction along the dorsal pathway. Can contour grouping deficits be explained in terms of the spatial frequency content of the display elements? To address the question, we tested patients and matched controls on three contour grouping paradigms in which the SF composition was modulated. In the Kanizsa task, subjects disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 104 publications
3
30
0
Order By: Relevance
“…Might age rather than illness duration explain why chronic patients more poorly integrate? To better address the issue, we combined the current data set with that of a previous study (Keane et al, 2014a), which ran control and chronic subjects with the same task design and inclusion/exclusion criteria. The pooled sample comprised 50 controls and 64 patients matched group-wise on age and gender.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Might age rather than illness duration explain why chronic patients more poorly integrate? To better address the issue, we combined the current data set with that of a previous study (Keane et al, 2014a), which ran control and chronic subjects with the same task design and inclusion/exclusion criteria. The pooled sample comprised 50 controls and 64 patients matched group-wise on age and gender.…”
Section: Resultsmentioning
confidence: 99%
“…Our task additionally has four response alternatives, which can generate an acceptable level of threshold uncertainty (i.e., 5%) with about half as many trials as when there are two response types (Jäkel & Wichmann, 2006). Finally, the tested paradigm incorporates high spatial frequency stimuli (scaled down in size), which—for reasons that are not fully understood—strongly exacerbate deficits in chronic patients (Keane et al, 2014a). Therefore, the current psychophysical procedure has methodological advantages over prior studies and has the potential to reveal differences that so far have gone undetected.…”
Section: Introductionmentioning
confidence: 99%
“…These findings provide evidence that perceptual learning-based visual training can improve real world skills used in daily life. Based on these results obtained with UE in non-psychiatric samples (Deveau, Lovcik, et al, 2014; Deveau, Ozer, et al, 2014; Deveau & Seitz, 2014), as well as the findings of intact perceptual learning ability in schizophrenia described above (e.g., Keane et al, 2014), we hypothesized that among individuals with schizophrenia, UE training would lead to improvements on the “trained task” of contrast sensitivity, as well as in central visual acuity and perceptual organization. In this preliminary report, we illustrate the implementation and effects of the UE visual perceptual training program with three individuals with schizophrenia.…”
Section: Introductionmentioning
confidence: 87%
“…With the JOVI and other similar CI tasks, studies have shown that people with schizophrenia are less able to detect and make shape judgments about fragmented contours when compared to various healthy and psychiatric control groups (Butler et al, 2013; Feigenson, Keane, Roche, & Silverstein, 2014; Keane, Erlikhman, Kastner, Paterno, & Silverstein, 2014; Keane et al, 2012; Kozma-Weibe et al, 2006; Schallmo, Sponheim, & Olman, 2013a, 2013b; Schenkel, Spaulding, DiLillo, & Silverstein, 2005; Schenkel, Spaulding, & Silverstein, 2005; Silverstein et al, 2009; Silverstein et al, 2006; Silverstein et al, 2012; Silverstein, Kovacs, Corry, & Valone, 2000; Uhlhaas, Phillips, Schenkel, & Silverstein, 2006; Uhlhaas, Phillips, & Silverstein, 2005). Past CI studies in schizophrenia have also demonstrated that, while performance does not vary from the acute to stabilization phases of illness in briefly hospitalized (i.e., ~2 weeks) patients (Feigenson et al, 2014), it becomes worse with longer illness chronicity and a lower level of functioning (Schenkel, Spaulding, & Silverstein, 2005; Silverstein et al, 2006; Uhlhaas et al, 2005).…”
Section: 0 Introductionmentioning
confidence: 99%